Oil in the Ecosystem: Chronic Exposure, Bioaccumulation, and Emerging Health Risks - Altawell, Najib; Plavan, Gabriel; Ebadi, Abdol Ghaffar; Selamoglu, Zeliha (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
Aquatic ecosystem oil pollution is a ubiquitous and persistent environmental hazard with extensive ecological and human health implications. Unlike acute petroleum hydrocarbon spillings, chronic low-level exposure to petroleum hydrocarbons—primarily polycyclic aromatic hydrocarbons (PAHs)—leads to long-term sediment pollution, bioaccumulation in aquatic life, and trophic transfer via food webs. This mini-review combines current understanding of chronic exposure to oil with specific attention to the ecological processes of bioaccumulation, toxicokinetics of chemicals from oil, and what they mean for environmental and public health. Chronic petroleum contaminants can potentially alter cellular, genetic, and endocrine processes in aquatic and terrestrial animals. Chronic dietary exposure to oil-exposed seafood has been linked with increased risks of carcinogenesis, developmental toxicity, and immunosuppression in humans. New advances in biosensors, isotopic tracing, and metabolomics are advancing our understanding of chronic exposure pathways and biological effects. Moreover, the review highlights the emerging role of microbial remediation and green technologies in minimizing oil pollution impacts. Much progress has been made, but gaps remain in bridging ecological exposure to health outcomes at the population level. This article advocates for an integrative risk assessment approach that combines environmental toxicology, public health surveillance, and ecosystem modeling to address the complex impacts of oil pollution. It concludes with future research recommendations, monitoring practices, and policy reform.